Thermal Decomposition Kinetics of Labile Chromium Complex with Benzoic Acid - M. K. Mishra; N. M. Misra (E-Journal of Chemistry)
Complex [CrO2 (C7H5O2) C2H5OH) (H2O)2] was prepared by using benzoic acid. Its spectral characterization was done by using Elemental analysis (C and H), Inductively coupled plasma optical emission spectroscopy (ICP - OES), Ultraviolet - visible (UV-Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and Fast Atomic Bombardment (FAB) Mass spectrometry. Whereas thermal decomposition was investigated by differential scanning calorimetric (DSC). The low value of activation energy of exothermic change indicated lability of complex.